1996
DOI: 10.1111/j.1095-8649.1996.tb01111.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing Sr/Ca ratios in otoliths of Girella elevata: an experimental investigation

Abstract: The utility of Sr/Ca ratios in otoliths as indicators of thermal history in fish was investigated for juvenile Girella elevata. There was no direct relationship between ratios of Sr/Ca and temperature of the water, as has been assumed in many previous studies. Sr/Ca ratios did not decrease when water temperature was elevated from 19 to 28 C. Elevation of ambient Sr levels in the sea water caused a significant increase in Sr/Ca ratios in otoliths, and there was a detectable increase in Sr/Ca ratios in otoliths … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 34 publications
1
54
0
Order By: Relevance
“…In those studies that altered dietary intake of elements, several authors reported no influence of diet (Hoff & Fuiman 1995, Milton & Chenery 2001, while others found detectable effects of diet on otolith chemistry (Limburg 1995, Gallahar & Kingsford 1996, Buckel et al 2004. Of the studies that reported detectable dietary effects on otolith chemistry, Limburg (1995) and Gallahar & Kingsford (1996) found small effects on otolith Sr content when fish were fed Sr-spiked food. Buckel et al (2004), however, reported that Sr increased by approximately 20% and Ba increased by 100% in otoliths of juvenile bluefish fed prey that differed in Sr and Ba concentration by approximately 250%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In those studies that altered dietary intake of elements, several authors reported no influence of diet (Hoff & Fuiman 1995, Milton & Chenery 2001, while others found detectable effects of diet on otolith chemistry (Limburg 1995, Gallahar & Kingsford 1996, Buckel et al 2004. Of the studies that reported detectable dietary effects on otolith chemistry, Limburg (1995) and Gallahar & Kingsford (1996) found small effects on otolith Sr content when fish were fed Sr-spiked food. Buckel et al (2004), however, reported that Sr increased by approximately 20% and Ba increased by 100% in otoliths of juvenile bluefish fed prey that differed in Sr and Ba concentration by approximately 250%.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, water was thought to contribute most to the composition of calcareous structures in teleosts (Schiffman 1961, Berg 1968, Simkiss 1974, Hoff & Fuiman 1995, Farrell & Campana 1996, Gallahar & Kingsford 1996. However, dietary composition may also influence otolith chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…Element composition of biogenic aragonites is thought to depend mainly on physicochemical properties of the surrounding water (Campana 1999). Nevertheless, it has been repeatedly reported that endogenous factors such as diet might have an eVect on the element compositions of Wsh otoliths (Limburg 1995;Farrell and Campana 1996;Gallahar and Kingsford 1996;Buckel et al 2004) as well as cephalopod statoliths (Zumholz et al 2006), since cations entering the inner ear endolymph via the blood circuit can originate either from branchial or intestinal uptake (Campana 1999). Previous investigations on the importance of food on element incorporation into otoliths were highly ambiguous.…”
Section: Introductionmentioning
confidence: 99%
“…Walther and Thorrold (2006) concluded that Sr and Ba contents in marine Wsh otoliths clearly reXect ambient Sr and Ba concentrations, while Kennedy et al (2000) reported 70% of the Sr isotopic signature in freshwater Atlantic salmon (Salmo salar) otoliths to originate from food. SigniWcant dietary eVects on strontium incorporation have been demonstrated for American shad (Alosa sapidissima) (Limburg 1995) and Black bream (Girella elevata) (Gallahar and Kingsford 1996) and for strontium and barium incorporation in blueWsh (Pomatomus saltatrix) (Buckel et al 2004). No eVects were detected for the uptake of magnesium, potassium, strontium, sodium, and calcium in Red drum (Sciaenops ocellatus) (HoV and Fuiman 1995), for strontium, copper and lead in barramundi (Milton and Chenery 2001), for sodium, magnesium, potassium, calcium and manganese in blueWsh (P. saltatrix) (Buckel et al 2004) and for strontium in Japanese eel (Anguilla japonica) (Lin et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Mn). Chemical marking studies using Sr have also found a relationship between Sr concentration in otoliths (and bone) and ambient Sr concentrations (Gallahar & Kingsford 1996, Pollard et al 1999. Geffen et al (1998), however, found an inverse relationship between exposure and rate of lead incorporation in otoliths.…”
Section: Spatial Differences In Elemental Composition Of Otolithsmentioning
confidence: 99%